If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 12 = 10x + -18 Reorder the terms: 12 + 8x = 10x + -18 Reorder the terms: 12 + 8x = -18 + 10x Solving 12 + 8x = -18 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 12 + 8x + -10x = -18 + 10x + -10x Combine like terms: 8x + -10x = -2x 12 + -2x = -18 + 10x + -10x Combine like terms: 10x + -10x = 0 12 + -2x = -18 + 0 12 + -2x = -18 Add '-12' to each side of the equation. 12 + -12 + -2x = -18 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = -18 + -12 -2x = -18 + -12 Combine like terms: -18 + -12 = -30 -2x = -30 Divide each side by '-2'. x = 15 Simplifying x = 15
| (3m+8n)(3m-8n)= | | 12=3b+6a | | 5(10y-2)=2(2y+20) | | a+15=18 | | 50x+278=850 | | 16x-43=-33 | | 0=x^2+8x-16 | | -3=-3(1-4a) | | 7x-9=3x+31 | | 3.21-7y=10y-1.84 | | 29x^2-29x=0 | | t-1.3=-5.3 | | 7x+8=5x+10 | | (1-9a)(1-7a)= | | 3x-4+2x=21 | | (1-4a)(1-9a)= | | -3(X+4)=-8X | | 2y-2x=14 | | x^2+2x-63= | | -6(-6k+7)-8k=70 | | x*x-x=.3125 | | a+25=18 | | 4m-5=15 | | 3(6)-5=y | | -3(x+3)-5(1+7x)=62 | | 3c+12=-7 | | x+2+3x-4+5=15 | | x+4.3=-2.7 | | 2a+13=21 | | -60=-6(-8x+2) | | 4r^2-23r-6=0 | | 4(6)-y=7 |